Medical encounters among 94,033 race starters during a 16.1-km running event over 3 years in the Netherlands: SAFER XXVI - Sewry, N.; Wiggers, T.; Schwellnus, M. (Sports Health: A Multidisciplinary Approach, 2023)
Background There are limited data on the medical encounters (MEs) occurring during mass community-based running events of shorter distances (10-21.1 km). The aim of this study was to determine the incidence and nature of MEs during the largest mass participation running event in the Netherlands.